Undesirable side-effects of water hyacinth control in a shallow tropical reservoir - Bicudo, Denise de Campos (2016)
Made available in DSpace on 2016-10-10T03:51:12Z (GMT). No. of bitstreams: 2 Undesirable side-effects of water hyacinth control in a shallow tropical reservoir.pdf: 907580 bytes, checksum: 7ee2b7360d1942ed6839e83325fa22ee (MD5) license.txt: 1818 bytes, checksum: 46de3043f08e87659ae535ef74b8ce9d (MD5) Previous issue date: 2007-06